PENGARUH Pengaruh Mengunyah Buah Kiwi (Actinidia Deliciosa) Terhadap Gingivitis Pada Seluruh Siswa Kelas VII di SMPN 3 Banjarbaru - Dwi Ani Rianti; Metty Amperawati; Naning Kisworo Utami; Rasuna Ulfah (Poltekkes Kemenkes Banjarmasin, 2026)
Gingivitis is a gum inflammation commonly caused by bacterial infection. Indonesia is one of the countries ranked second with a gingivitis prevalence rate of 96.58%. Dental and Oral Health Problems in South Kalimantan province are 15.29% in the city of Banjarbaru, the gingivitis rate reaches 6.74% (Riskesdas, 2018). According to Riskesdas data in 2018, there was an increase from 23.5% in 2013 to 59.6% in 2018. The purpose of this study is to determine the effect of chewing kiwifruit (Actinidia Deliciosa) on gingivitis in all grade VII students at State Senior High School 3 Banjarbaru. This type of research is analytics with pseudo-experiments. The design used is One Group Pre-test Post-test. The population is all grade VII students at all grade VII students at State Senior High School 3 Banjarbaru, which is 220 people with a sample of 79 people. Sampling was done using the Purposive sampling technique, with statistical analysis of the Paired Sample T- test. The study results showed that the average gingivitis score before chewing kiwi fruit was 1.5, while after chewing kiwi fruit it decreased to 1.0, with a difference of 0.5. The statistical test showed a p-value of 0.000, which is less than α = 0.05, indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. In conclusion, there is an effect of chewing kiwifruit (Actinidia Deliciosa) on gingivitis in all grade VII students at State Senior High School 3 Banjarbaru. It is recommended to be able to use kiwifruit (Actinidia Deliciosa) as a natural remedy that is capable of healing and preventing gingivitis.